# Solve the formula for the specified variable. I don't understand the following:

s=2*pi*r*h + 2*pi*r^2 for h

-the options for this one are:

a. h=(s)/(2*pi*r)-1

b. h=2*pi(s-r)

c. h=(s-2*pi*r^2)/2*pi*r

d.h=s-r

A=P(1+nr) for r

-the options for this one are:

a. r= a-p/pn

b.r=a/n

c.r= p-a/pn

d. r= pn/a-p

1. Check whether you copied option "a" correctly. Unless the last term is r instead of 1, none of the choices are correct.

2. Unless there are parentheses around (a-p), noe of the choices are correct. Try to avoid mixing up upper and lower case sumbols.

## For the first equation, s = 2πrh + 2πr², we want to solve for h. Here's how we can do that:

Step 1: Start by isolating the term with h on one side of the equation.

Subtract 2πr² from both sides:

s - 2πr² = 2πrh

Step 2: Next, divide both sides of the equation by 2πr to solve for h.

(s - 2πr²) / (2πr) = h

Step 3: Simplify the right-hand side, if possible.

h = (s - 2πr²) / (2πr)

So, the correct answer for solving the equation s = 2πrh + 2πr² for h is:

c. h = (s - 2πr²) / (2πr)

Now, let's move on to the second equation, A = P(1 + nr) for r.

Step 1: Start isolating the term with r on one side of the equation.

Divide both sides of the equation by P:

A / P = 1 + nr

Step 2: Rewrite the left-hand side as a fraction (A/P) and isolate the term with r.

A / P - 1 = nr

Step 3: Finally, divide both sides of the equation by n to solve for r.

(A / P - 1) / n = r

So, the correct answer for solving the equation A = P(1 + nr) for r is:

b. r = (A / P - 1) / n

Please note the corrections mentioned at the beginning of the response regarding the provided answer choices.